Infertility problems in dairy cattle: Causes and prevention - Khan, M H; Kumar, Suresh (Indian Farming, 2016)
Normal reproduction is a basis for sound animal husbandry. Because of the relatively long estrous as well as reproductive cycles, impaired fertility leads to considerable loss of time during which production is eithe reduced or ceases entirely. Prevention of this loss is far more effective measure than attempts to correct impairment after considerable time and production have already been lost. Herd fertility examination depends upon type of breed as well as on husbandry practices employed. The progressive dairy husbandry can not be maintained on a high level unless calving intervals are kept at minimum. Regular, accurate evaluation of fertility status of dairy herd is an essential part of a control programme and should be done at least twice a year.